WORLD SKILLS CHAMPIONSHIP MOVEMENT: INTRODUCING CONVERGENT TECHNOLOGIES INTO THE SYSTEM OF TRAINING HIGHLY QUALIFIED PERSONNEL IN THE SPECIALTY OF “AGRONOMY” - N V Belyakov (Universitas Brawijaya, 2019)
The article deals with the problems of training qualified personnel in the direction of “Plant Protection”. World Skills movement serves as a convergent training technology in accordance with international standards. The author justifies the introduction into the World Skills competencies movement “Agronomist. Plant Protection” and “Entrepreneurship in the environmental field”.